On some proporties of Frege proofs - Sona R. Aleksanyan; Anahit A. Chubaryan (Изд-во НАН РА)
In [4] a measure s on propositional formula was de¯ned such that for every tautology φ "high" value of s(φ) requires the large size of proof in the "weak" propositional systems. In this paper it is shown, that there is a tautology φ, the measure s(φ) of which has exponential dependence on the size of φ, but its proof complexity in Frege systems is polynomially bounded.
Keywords: Mathematics